PEMBERDAYAAN MASYARAKAT DALAM UPAYA MEWUJUDKAN DESA LABORATORIUM MANAJEMEN BENCANA GUNUNG BERAPI - Agus Khoirul Anam; Sri Winarni; Andi Hayyun Abiddin (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
A miniature of the community affected by volcanic disasters that occurred within a certain period of time can be used as a learning laboratory in disaster management preparedness. This community service activity aims to empower DESTANA cadres (Tangguh Bencana Village) and community leaders in realizing the village of a Volcano Disaster Management Laboratory in Dusun Candisewu, Blitar Regency. The mentoring introspective method was used in an implementation of a volcano disaster management laboratory. The results of this program demonstrated the realization of a volcano disaster management laboratory in Candisewu. The conclusion of this activity is DESTANA cadres and the community are able to actively participate in realizing a volcano disaster management laboratory, increasing the capacity of the community in mitigating volcanic eruption disasters. Suggestions need to be increased efforts to complete facilities and infrastructure related to disasters.